Designing Integrated Inventory Learning in Logistics Vocational High School - Dwiyanti, Vina; Okitasari, Hanissa; A., Ana; Ismail, Affero (Journal of Technical Education and Training, 2026)
The logistics industry is rapidly developing, providing opportunities for vocational high school/Sekolah Menengah Kejuruan (SMK) students majoring in Logistics Engineering to fill various occupational roles. Inventory is one of the logistics activities studied by SMK Logistics Engineering students. Learning that does not align with real industry conditions becomes an obstacle for students in understanding what needs to be done. This research aims to design interactive and integrated inventory learning for logistics. The research method used is a qualitative approach with Focus Group Discussions (FGD) as the primary data source, conducted with stakeholders including logistics vocational teachers, logistics experts, practitioners, students and lectures,  along with secondary data from the logistics curriculum for SMK. The results indicate that there are six main cores that need to be incorporated into inventory learning, which include Concept and Flow, Inventory Control Methods, Cost Structure, Actual Case Studies, Related Documents, and Reporting Mechanism. Inventory learning will be more integrated if technology is used as an interactive and engaging learning aid, helping students fully and accurately understand inventory activities.